Cell-cell contacts in the human cell line ECV304 exhibit both endothelial and epithelial characteristics - Kießling, Fabian; Kartenbeck, Jürgen; Haller, Christlieb (Cell & tissue research, 1999)
Endothelial cells separate the intra- and extravascular space and regulate transport processes between these compartments. Since intercellular junctions are required for these specific cell functions, the cell-cell contacts in the permanent cell line ECV304 were systematically analyzed and compared with human umbilical vein endothelial cells (HUVECs) in primary culture and with the epithelial Madin Darby Canine Kidney (MDCK) cell line. Filter-grown ECV304 cells generate a distinct electrical resistance and a permeability barrier between cell culture compartments. Electron microscopy of ECV304 cells revealed lateral membrane interdigitations, typically found in endothelial cells in vivo, with direct membrane contact sites, which prevented the diffusion of lanthanum. By immunoblot and immunofluorescence analysis, the expression and cellular localization of the tight junction and adherens-type junction proteins occludin, ZO-1, symplekin, β-catenin, and plakoglobin were analyzed. ECV304 cells display further characteristics of endothelial cells, including the expresssion of thrombomodulin and of the vitronectin receptor CD51, as well as the secretion of plasminogen activator inhibitor 1 (PAI-1) and endothelin. However, ECV304 cells also express proteins characteristically found in epithelial cells, including E-cadherin and the desmosomal proteins desmoplakin, desmocollin, and desmoglein; occasionally desmosomal structures can be identified by electron microscopy. In conclusion, ECV304 cells express many endothelial markers and form specialized intercellular junctions that display some epithelial features. Thus this reportedly endothelial-derived permanent human cell line may be dedifferentiated toward an epithelial phenotype.